Mechanisms of Acetate in Alleviating SETDB1-Linked Neuroinflammation and Cognitive Impairment in a Mouse Model of OSA - Zhao Z; Xiang L; Hong JS; Wang Y; Feng J (Journal of Inflammation Research)
Zhan Zhao,1,* Li Xiang,1,* Jau-Shyong Hong,2 Yubao Wang,1 Jing Feng1 1Respiratory Department, Tianjin Medical University General Hospital, Tianjin, 300052, People’s Republic of China; 2Neurobiology Laboratory, National Institute of Environmental Health Sciences, National Institutes of Health, Research Triangle Park, Durham, NC, 27709, USA*These authors contributed equally to this workCorrespondence: Yubao Wang, Respiratory Department, Tianjin Medical University General Hospital, Tianjin, 300052, People’s Republic of China, Email yubaowang2020@hotmail.com Jing Feng, Respiratory Department, Tianjin Medical University General Hospital, Tianjin, 300052, People’s Republic of China, Email tmugh_fj@tmu.edu.cnBackground: Microglia-mediated neuroinflammation is crucial for obstructive sleep apnea (OSA)-induced cognitive impairment. We aimed to investigate roles of acetate (ACE) and SET domain bifurcated histone lysine methyltransferase 1 (SETDB1) in neuroinflammation of OSA.Methods: After C57BL/6J mice were exposed to OSA-associated intermittent hypoxia (IH) or normoxia for four weeks, the composition of the gut microbiota (GM) and the levels of serum short-chain fatty acids (SCFAs) were measured by 16S rRNA and GC-MS methods, respectively. To assess the effect of ACE on IH mice, glyceryl triacetate (GTA) was gavaged in IH-exposed mice and the cognitive function, microglial activation, and hippocampal neuronal death were examined. Moreover, ACE-treated BV2 microglia cells were also utilized for further mechanistic studies.Results: IH disrupts the gut microbiome, reduces microbiota-SCFAs, and impairs cognitive function. Gavage with GTA significantly mitigated these cognitive deficits. Following IH exposure, we observed substantial increases in SETDB1 both in vivo and in vitro, along with elevated levels of histone H3 lysine 9 trimethylation (H3K9me3). Genetic or pharmacological inhibition of SETDB1 in microglia led to decreased induction of proinflammatory factors, as well as reduced reactive oxygen species (ROS) generation. Mechanistically, SETDB1 was found to upregulate the transcription factors p-signal transducer and activator of transcription 3 (p-STAT3) and p-NF-κB. In vitro, ACE supplementation effectively repressed high SETDB1 and H3K9me3 levels, thereby inhibiting microglial pro-inflammatory responses induced by IH. In vivo, ACE supplementation significantly reduced hippocampal levels of p-STAT3, p-NF-κB, and pro-inflammatory cytokines while also protecting neuronal integrity.Conclusion: This study provides the first evidence that H3K9 methyltransferase SETDB1 promotes microglial pro-inflammatory response distinct from its previously shown role in macrophages. Our findings also identify ACE supplementation as a promising dietary intervention for OSA-related cognitive impairment with SETDB1 serving as both a mechanistic biomarker and potential therapeutic target.Keywords: acetate, neuroinflammation, OSA, SETDB1, NF-κB, STAT3